The Road Side Tests for Alcohol and Drugs in Traffic History Evolution and Usage in the Present Day - Aşırdizer, Mahmut; Hekimoğlu, Yavuz (The Bulletin of Legal Medicine, 2015)
In 1769, Nicolas-Joseph Cugnot's car hit a wall during test runs with steam power in France. This accident is considered as the first automobile accident in history. In a traffic accident occurred in 1897, a taxi driver, George Smith collided his car to a building and his car was damaged. This case recorded to history of traffic accidents as first case of driving under the influence of alcohol. Nowadays, traffic accidents have defined as one of most important problems of the world by high rates of morbidity and mortality as the parallel to the rise from past to present of the number of vehicles and population. In several previous studies, it was emphasized that there was a correlation with usage of drugs and alcohol of drivers and the number of traffic accidents and increasing of risk of injury and death due to traffic accidents. In this study, it was aimed compilation and submission of information on the history, evolution and usage of the road side tests in the present day, following the presentation of general information about the history of traffic accidents, status of a traffic accident today, and the effects of alcohol and drug use on traffic accidents.
Keywords: Traffic accidents, Alcohol, Drug, The road side tests, History